LEGAL PROTECTION OF COMPENSATION FOR VICTIMS OF INVESTMEN CRIME IN THE PERSPECTIVE OF ISLAMIC LAW - Santoso, Bambang; Arifin, Muhammad; Ramlan, Ramlan (Proceeding International Seminar of Islamic Studies, 2023)
Illegal investment crimes take many victims and cause huge losses for the victims, which have implications for disrupting the country's economic stability. The perpetrators are not only from within the country but across countries by using digital facilities. Islamic law strictly prohibits fraudulent acts in business and trade transactions, Islam threatens the perpetrators with severe punishment in this world and in the hereafter according to the word of Allah SWT in Surah Al-Muthoffifin verse 1 which means; "Woe to those who cheat". To protect the public from becoming victims of illegal investments, strong regulations and institutions are needed and strict sanctions are imposed on the perpetrators. The perpetrator must be held accountable for his actions both civilly and criminally, this is in accordance with the concept of al-mas'uliyat (legal responsibility) which is meant in the Shari'a, both criminal liability and criminal liability. Illegal investment crimes are very contrary to the principle of maqashidu syar'iyyah, therefore it is very appropriate to impose penalties on the perpetrators to compensate for the losses of the victims.